Animal Models of Brain Tumors - Martínez Murillo, Ricardo.; Martínez Murillo, Ricardo.; Martínez, Alfredo.; Martínez, Alfredo. (Neuromethods,, 2013)
Although the available models, whether at the cellular, tissue, or animal level, do not exactly represent the biology of human brain tumors, animal models can offer significant insights into these tumors, providing a better understanding of biological mechanisms underlying tumor generation, growth, angiogenesis, invasion, and metastasis.  Animal Models of Brain Tumors brings together developments and discoveries in “in vivo” experimental tumor research that have provided advances in our understanding of the cellular and molecular mechanisms involved in the generation, progression, and clinical outcome of brain neoplasms. Broken into convenient sections, this thorough volume includes topics such as animal model insights into human brain neoplasms, the cellular, molecular, and genetic basis of brain tumors,  therapies in the treatment of malignant glioma, as well as imaging technologies in animal tumor models, i.e. measuring brain tumor growth and metabolism.  Written for the popular Neuromethods series, chapters include the kind of detailed description and implementation advice that is essential for achieving successful results.   Authoritative and cutting-edge, Animal Models of Brain Tumors provides the key methods needed to validate, compare, and contrast the animal model with its proposed human counterpart and further the understanding of our own serious ailments.